2017
DOI: 10.1002/cctc.201701054
|View full text |Cite
|
Sign up to set email alerts
|

Nickel/USY Catalyst Derived from a Layered Double Hydroxide/Zeolite Hybrid Structure with a High Hydrogenation Efficiency

Abstract: It is important and challenging in heterogeneous catalysis to prepare catalysts with highly dispersed metal nanoparticles that have a high activity. Herein, a new Ni/USY catalyst derived from a core–shell NiAl‐LDHs/USY hybrid material has been prepared by the in situ growth of a layered double hydroxides (LDHs) precursor on the surface of USY zeolite crystals. Under the appropriate conditions, the adscititious Ni source interacted chemoselectively with Al species dissolved from the zeolite framework to form a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 64 publications
2
17
0
Order By: Relevance
“…Finally, (iii) has proven challenging as hydrogen is required for the saturation of unsaturated fatty acids, leading to attempts to produce in-situ hydrogen from solvents or from sacrificial reactions [11,12]. Recent work has attempted to tackle these concerns by introducing bifunctional catalysts which provide both hydrogenation activity and solid acid activity [13][14][15][16][17][18]. Zeolites offer highly desirable properties such as high surface areas, good chemical and thermal stability, and strong acidity as a support material for metals [19].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, (iii) has proven challenging as hydrogen is required for the saturation of unsaturated fatty acids, leading to attempts to produce in-situ hydrogen from solvents or from sacrificial reactions [11,12]. Recent work has attempted to tackle these concerns by introducing bifunctional catalysts which provide both hydrogenation activity and solid acid activity [13][14][15][16][17][18]. Zeolites offer highly desirable properties such as high surface areas, good chemical and thermal stability, and strong acidity as a support material for metals [19].…”
Section: Introductionmentioning
confidence: 99%
“…Supporting the LDHs phase on as uitable substrate could effectively maintain the layered structure and guarantee the exposure of active sites. [22] On the basis of previous findings, herein we disclose a unique USY@ZnO/Al 2 O 3 catalyst derived from aU SY@ZnAl-LDHs core-shell precursor.T he in situ growth process of USY@ZnAl-LDHs was investigated in detail by varying the synthesis temperature, pH value, Zn source, and ammonium source.A na dvanced and thorough characterizationw as employed to determinet he nature of the ZnAl-LDHs structure and variation in the coordination state of aluminum during the whole synthetic process. Then Zhao et al obtaineda ne venly dispersed ZnAl mixed-metal oxide on an Al 2 O 3 support by using al egumeb iotemplate, whiche xhibited higherp hotocatalytic activity than the corresponding metal oxide powder sample.…”
Section: Introductionmentioning
confidence: 53%
“…Upon reduction,t he resultant Ni/USY catalyst, with highly dispersed Ni nanoparticles precisely confined on the Al 2 O 3 matrix, possessed as lightly decreased surfacea rea and pore volume, which prevented the aggregation of Ni nanoparticles during thermalt reatment and guaranteed the sufficient exposure of active sites in the hydrogenation reaction. [22] On the basis of previous findings, herein we disclose a unique USY@ZnO/Al 2 O 3 catalyst derived from aU SY@ZnAl-LDHs core-shell precursor.T he in situ growth process of USY@ZnAl-LDHs was investigated in detail by varying the synthesis temperature, pH value, Zn source, and ammonium source.A na dvanced and thorough characterizationw as employed to determinet he nature of the ZnAl-LDHs structure and variation in the coordination state of aluminum during the whole synthetic process. The catalytic activity of the resultant USY@ZnO/Al 2 O 3 catalyst was then evaluated in Baeyer-Villiger (B-V) oxidation reactions with H 2 O 2 or tert-butyl hydroxide (TBHP) as the oxidant.…”
Section: Introductionmentioning
confidence: 53%
“…However, the isolated LDHs precursors are prone to suffer serious aggregation by ab ‐face stacking upon calcination, highly lowering the accessibility to the active centers in the resultant aggregated bulk multiple oxides ,. Previously, we found that the Al 3+ species in Al‐rich USY zeolite themselves could participate in the fabrication of NiAl‐LDHs structure, bridging the connection between zeolite crystal and LDHs phase . The as‐fabricated Ni/USY catalyst upon reduction possessed well‐preserved hierarchical porosity of USY zeolite with sufficient exposure of highly dispersed confined Ni nanoparticles on Al 2 O 3 matrix, which thereby exhibited remarkably enhanced hydrogenation activity for the hydrogenation of nitro aromatics.…”
Section: Introductionmentioning
confidence: 96%